God as Mother: A Feminine Theology in India - Mario Belotti (Journal of Dharma, 1977)
Many Hindu thinkers, teachers and writers from at least the early Christian centuries have deeply involved themselves with the problem of the feminine and masculine dimensions of ultimate reality. This attempt to come to terms with the bi-sexual nature of reality meets the claim of today's society for an equality of rights between men and women, and particularly for a new respect for womanhood. In his study of the Brahma Vaivarta Purana, a Sanskrit text that assumed its present shape perhaps as late as the 15th century A. D., C. Mackenzie Brown arouses an appreciation for a feminine theology.